Faktor yang Berdampak pada Profitabilitas Perusahaan : Peringkat Kinerja Lingkungan dan Pengungkapan Lingkungan - Rachman, Raisa Hanifa; Ririh Dian Pratiwi; Anna Sumaryati; Ngurah Pandji Mertha Agung Durya (Universitas Pasundan, 2025)
The purpose of this study is to provide an analysis of the impact of environmental performance and environmental disclosure on profitability in mining companies listed on the IDX in 2019-2022. The quantitative method used in the study shows the results that environmental performance has no influence on profitability in companies listed on the IDX in 2019-2022. This study has limitations in that it only uses two independent variables and the mining sector on the IDX. Suggestions that can be given are to add independent variables, research years, and sectors studied.